The Effect of Variations in Cocoa Shell Carbon on the Characteristics of Environmentally Friendly Stamp Ink - Sari, sinta widya; Masthura, Masthura; Husnah, Miftahul (Universitas Islam Negeri Ar-Raniry, 2025)
Cocoa plants produce cocoa fruit that can be used to make chocolate. There is 75% cocoa shell waste, from 25% cocoa beans. The cellulose content of cocoa shells ranges from 23-54%. This study aims to utilize cocoa shells as carbon for making environmentally friendly stamp ink. The variations of cocoa shell carbon used are 30 grams, 35 grams, 40 grams and 45 grams. The making of stamp ink is done by cocoa shell carbon , then the carbon is ground and vacuumed with a 100 mesh sieve. The carbon powder is added with 15 ml of polyethyelene glycol, 35 ml of alcohol and 50 ml of distilled water in each variation. The characteristic of stamp ink include density, viscosity, drying time, rubbing resistence, pH and color pihment. The best result are in the 30 gram variation with a density value of 1,015 g/cm³, viscosity of 2,50 poise, drying time of 8 seconds, the ink rubbing resistance does not fade. A ph of 8.5 is alkaline and produces black pigments.